Developing Manageable Individualised Formative Assessment of Translator Trainees Through Rubrics - Way, Catherine (Research in Language, 2021)
For some time now I have implemented a manageable combined assessment approach emphasising competence and decision-making (Way 2008, 2009). To do this, we must be able to monitor trainees’ planning, monitoring, regulating, evaluating, recognition of flawed and successful processes and task variables during their assignments. The question is: How can translator trainers assess such a vast range of complex processes? One possible solution is through rubrics for each trainee project management role and for the final translation. In this proposal we attempt to counterbalance the multiple demands of trainee assessment, whilst also addressing the time constraints on trainers and the opinions of trainees. In our paper we will present the rationale for the rubrics (after the pilot trial February-June 2020), one rubric example, an example of the Support Sheets for trainees and the outline for a platform which, once constructed, will only require periodical updating by trainers.